Plasma Wind Tunnel Investigation of European Ablators in Nitrogen/Methane Using Emission Spectroscopy. (19th June 2013) - Wernitz, Ricarda; Eichhorn, Christoph; Marynowski, Thomas; Herdrich, Georg
Abstract : For atmospheric reentries at high enthalpies ablative heat shield materials are used, such as those for probes entering the atmosphere of Saturn's moon Titan, such as Cassini-Huygens in December, 2004. The characterization of such materials in a nitrogen/methane atmosphere is of interest. A European ablative material, AQ60, has been investigated in plasma wind tunnel tests at the IRS plasma wind tunnel PWK1 using the magnetoplasma dynamic generator RD5 as plasma source in a nitrogen/methane atmosphere. The dimensions of the samples are 45 mm in length with a diameter of 39 mm. The actual ablator has a thickness of 40 mm. The ablator is mounted on an aluminium substructure. The experiments were conducted at two different heat flux regimes, 1.4 MW/m 2 and 0.3 MW/m 2 . In this paper, results of emission spectroscopy at these plasma conditions in terms of plasma species' temperatures will be presented, including the investigation of the free-stream species, N2 andN 2 +, and the major erosion product C2, at a wavelength range around 500 nm–600 nm.